2006
DOI: 10.1063/1.2360773
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dislocations on open circuit voltage in crystalline silicon solar cells

Abstract: The dislocation dependence of open circuit voltage is studied based on Donolato's model for the effect of dislocations on minority carrier effective diffusion length [J. Appl. Phys. 84, 2656 (1998)]. Experimental data measured on thin-film solar cells show a strong decrease of open circuit voltage V-oc with an increase in defect density. The analysis of the recombination currents indicates that V-oc is largely reduced by space charge region recombination. For a quantitative study on the relationship between di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…The boundary conditions at z = 0 and at x = y = ± a are again given by equations (3), (5), and (6). The boundary condition for hole concentration at the junction is…”
Section: Derivations Of Expressions For Dark Current Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The boundary conditions at z = 0 and at x = y = ± a are again given by equations (3), (5), and (6). The boundary condition for hole concentration at the junction is…”
Section: Derivations Of Expressions For Dark Current Componentsmentioning
confidence: 99%
“…Dislocations and other crystal defects in a wafer are known to have adverse effect on the cell performance, and in the case of multicrystalline silicon (mc‐Si), they strongly control the cell efficiency. Most of the studies on the effects of dislocations on the cell performance are carried out experimentally . However, it is fruitful to have accurate model to evaluate the effects of dislocations on various cell parameters such as short circuit current density ( J sc ), open circuit voltage ( V oc ), and fill factor.…”
Section: Introductionmentioning
confidence: 99%
“…Crystalline defects-such as grain boundaries [3] and dislocations [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]-impurities [20,21], and foreign inclusions [22][23][24] in mc-Si wafers degrade the PV performance of mc-Si solar cells. In order to enhance the PV performance of mc-Si solar cells, a lot of effort has been devoted to reducing the number of grain boundaries and the dislocation densities in mc-Si [7,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…The reduction of the diffusion length for an increasing dislocation density was modeled by Donolato [5]. On the basis of Donolato's work, Kieliba et al [6] studied the decrease of the open circuit voltage V oc for increasing dislocation densities. In an earlier work, we showed that this applies also for defect clusters [7].…”
Section: Introductionmentioning
confidence: 99%